SIGNIFICANCE OF SERUM INHIBIN IN FEMALE INFERTILITY - ullah, Sami; Ditta, Allah; Jaffery, Ghazala; Tayyab, Muhammad (Journal of Ayub Medical College Abbottabad, 2001)
Background: Serum inhibin, a glycoprotein hormone is secreted from granulosa cells in females and has been shown to suppress secretions of FSH from pituitary. Methods: A total of 45 women, 30 infertile subjects and 15 age matched fertile controls were included in this study. Blood samples from each subject were collected during follicular and luteal phases separately and were tested for serum inhibin levels using an enzyme linked immunosorbent assay (ELISA). Results: Serum inhibin concentration of infertile subjects during follicular phase was 35.5 ± 22.94 pg/ml and luteal phase was 32.4 ± 24.2 pg/ml. Whereas serum inhibin level in follicular phase was 10.39 ± 2.03 pg/ml and luteal phase was 12.78 ± 6.86 pg/ml of the fertile subjects. Serum inhibin was significantly raised in the infertile subjects as compared to the fertile subjects (P < 0.05). However, serum inhibin concentration during the follicular and luteal phases of the infertile subjects was not significantly different (P>0.05). Conclusion: It is thus concluded that increased serum inhibin level may be treated as sensitive and early index of declining ovarian function